My "T" Sound Box - Moncure, Jane Belk.; Thornburgh, Rebecca McKillip (Mankato, MN : Child's World, 2009)
Little t has an adventure with items beginning with his letter's sound, such as a toad, two turtles, and a tiger with tooth troubles.
Keywords: Alphabet